EFFECT OF UNIAXIAL INITIAL STRESSES, PIEZOELECTRICITY AND THIRD ORDER ELASTIC CONSTANTS ON THE NEAR-SURFACE WAVES IN A STRATIFIED HALF-PLANE - Kurt, I.; Akbarov, S. D.; Sezer, S. (YILDIZ TECHNICAL UNIV, 2017)
Dispersion curves of a system consisting of a piezoelectric covering layer and metal half-plane under the uniaxial initial stresses perpendicular to the wave propagation direction are obtained within the scope of the Three-dimensional Linearized Theory of Elastic Waves in Initially Stressed Bodies. The elasticity relations of the metal half-plane material are described by the Murnaghan potential. The numerical results are discussed for PZT-2 covering layer and aluminum half-plane material. The influence of the initial stresses, the piezoelectricity of the covering layer, and the third order elastic constants on the near-surface wave propagation velocity is illustrated.
Keywords: Uniaxial Initial Stress; Dispersion; Near-Surface Waves; Piezoelectric; Third Order Elastic Constants; PROPAGATION BEHAVIOR; LOVE WAVES; Thermodynamics